Influence of inoculum, particle size and inoculum-substrate ratio on CH4 production from Ulex sp. - Costa, J. C. (2014)
The performance of Anaerobic Digestion (AD) of solids wastes is affected by several factors. Most of them are related to each other. Currently, publish studies about AD only care about the individual influence of these variables, discarding possible interaction. A response surface experimental design was used to determine the most important variables and possible interactions – influence of inoculum type (anaerobic suspended sludge and granula sludge), Ulex sp. particle diameter (dp) and inoculum to substrate ratio (ISR) – on the Biochemical Methane Potential (BMP) and the maximum initial methane production rate (k). BMP and k of Ulex sp. varied between 153-308 L CH4 kg-1 VS and 14-49 L CH4 kg-1 VS d-1, respectively. Higher ISR and a mixture of granular and suspended sludge had a positive effect on the biodegradability of waste. A dp of 1.85 mm were defined as the optimal condition to simultaneously maximize the BMP and k.